Nonspecific External Arguments in Turkish - Sarah Kennelly (Dilbilim Araştırmaları Dergisi)
The proposal that nonspecific arguments obligatorily remain within VP has long been a topic of discussion (Enç 1991; Diesing 1992 among others). In Turkish I propose that the constraint is even stronger; nonspecific arguments are contained in VP (Kennelly to appear) as an internal argument1, never as an external argument in a Specifier position. Hence they are never subjects. By means of a study of Turkish Relative Clauses (RCs) it will be shown that nonspecific logical subjects of Unaccusatives (including Existentials and Passives) remain as internal arguments with Weak Case. This analysis then predicts that Transitive and Unergative verbs in Turkish will never have a nonspecific subject because they are base generated as external arguments in Spec.VP. In Section II the problematic data is introduced and the analysis proposed. The asymmetry of RCs is presented in Section III, which is then applied to the data in Section IV. When the internal argument of an Unaccusalivc verb is nonspecific, it must remain contained within VP and verb adjacent.